Health effects of caring for and about parents and spouses - Judith Bom; Pieter Bakx; Erik Schut; Eddy van Doorslaer (Tinbergen Institute, 2018)
Informal caregiving is a potentially attractive alternative to formal care but may entail health costs for the caregiver. We examine the mental and physical health impact of providing informal care and disentangle the caregiving effect – the effect of caring for someone in need – from the family effect – the effect of caring about someone in need. We account for potential endogeneity in the caregiving decision and control for previous health status using Arellano-Bond difference GMM models. We use four waves (2010-2013) of panel data from the Dutch Study on Transitions in Employment, Ability and Motivation (STREAM). We find that caregiving harms the mental health of caregivers; this effect is mainly present for spousal caregivers. A negative health shock of a family member also has a direct negative effect on mental health, providing evidence of a family effect. These findings imply that most studies may have overestimated the negative health effects of caregiving by not accounting adequately for the family effect. As the caregiving effect differs strongly between various types of caregivers, policies to counteract this effect should specifically target subgroups of caregivers that carry the largest burden of informal caregiving.
Keywords: J14; I10; J18; 330; long-term care; informal care; caregiver effect; family effect; mental health